Causes and outcomes of new onset status epilepticus and predictors of refractoriness to therapy. (April 2016) - Jayalakshmi, Sita; Vooturi, Sudhindra; Sahu, Sambit; Yada, Praveen Kumar; Mohandas, Surath
Highlights: Nearly half of patients with new onset Status Epilepticus (SE) progressed to Refractory SE (RSE). New onset RSE patients were younger than New onset SE patients. Cryptogenic etiology was associated with progression of new onset SE to RSE. Outcome was similar between symptomatic and cryptogenic new onset RSE. Abstract: We aimed to evaluate the determinants of outcome in new onset refractory status epilepticus (SE). A retrospective analysis of patients with new onset SE admitted between May 2005 and October 2013 was performed. Regression analysis was used to determine factors that affect progression of new onset SE to refractory status epilepticus (RSE) and mortality. Among 114 patients with new onset SE, 52 patients progressed to RSE. Sixty seven (58.7%) were men. New onset RSE patients were younger than new onset SE patients (mean 35.9 ± standard deviation18.2 versus 28.7 ± 20.2 years; p = 0.050). Cryptogenic aetiology was the most significant determinant of progression of new onset SE to RSE (Exp [β] = 5.68; p = 0.001). The overall mortality in the entire group was 23.7%, significantly higher in new onset RSE group (40.4% versus 9.7%; p < 0.0001). New onset RSE patients with symptomatic and cryptogenic etiology did not differ for clinical characteristics and outcome. Acidosis was the strongest predictor of mortality in the entire cohort (Exp [β] = 8.72; p = 0.005). Nearly half of the patients with new onset SE progressed to RSE. While cryptogenic aetiology determined progression of new onset SE to RSE, acidosis was associated with mortality. The outcome was similar between symptomatic and cryptogenic new onset RSE.